The Structure of the Romanian Dual Education System - Constantin CUCOSEL (Communications of International Proceedings, 2021)
The initial professional development and educational process has a direct impact on employment policies, being one of the European priorities and strategies in this field. The recent transformation processes of society, the transition toward a knowledge-based society are all challenges faced by the educational system. Besides ensuring access to education and acquiring a high level of qualification, the relevance and quality of training of those who study becomes significant. In this context, ensuring the quality of professional and technical education receives new valences and requires new institutional roles.
Keywords: Management; Education; Dual Education; Technical Education; Economic Operators; Qualification